Books and Monographs Received (Review of Economic Studies, 1935)
Books and Monographs Received Get access The Review of Economic Studies, Volume 2, Issue 3, June 1935, Page 245, https://doi.org/10.1093/restud/2.3.245 Published: 01 June 1935